Studi Komparasi Jarh wa Ta’dil dengan Kajian Islam Modern - Fadllurrahman, Irfan; Arifin, Tajul (Darul Yasin Al Sys, 2024)
This paper investigates the comparison between Jarh wa Ta'dil and modern Islamic studies in understanding the history of the Prophet Muhammad (PBUH). Utilizing the theory of Islamization of knowledge proposed by Raj Ismail al-Faruqi, the researcher seeks to find a middle ground between these two disciplines. The Islamization of knowledge aims to enrich Islamic scholarship by incorporating not only pure Islamic sciences but also modern knowledge. This involves strengthening modern sciences, problem-solving methods, understanding issues, and providing solutions. Jarh wa Ta'dil, which primarily focuses on the chain of narration (sanad), and modern Islamic studies, which dominate the study of the text (matan), can be synergized and made complementary. This would create a harmonious relationship between the two scholarly approaches. In essence, the historical study of Islam will be stronger through the discipline of Jarh wa Ta'dil, ensuring the credibility of transmission validity, while interpretation will be supported by modern Islamic studies. The conclusion is that there is no need to contradict the two approaches, but rather they can mutually reinforce each other. For example, in the case of Isra' Mi'raj, Jarh wa Ta'dil is necessary to obtain the complete narrative data, which can then be analyzed with modern scientific approaches to further develop and sharpen the understanding of this spectacular miracle.